1998
DOI: 10.1590/s0074-02761998000700004
|View full text |Cite
|
Sign up to set email alerts
|

Role of cytokines in the formation and downregulation of hepatic circumoval granulomas and hepatic fibrosis in Schistosoma mansoni-infected mice

Abstract: Variations in the size of granulomas in acute (8 week) infections may be influenced primarily by the number and state of activation of T cells. In chronic (12-16 week) infections immunologic downmodulation proceeded normally in mice without functional CD8+ cells and in IFN-g KO mice but not in B cell KO (mMT) mice or in mice deficient in FcR expression in spite of the fact that these mice downregulated their T cell and cytokine responses. It is evident that the participation of cytokines in granuloma formation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
23
0

Year Published

1999
1999
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 57 publications
3
23
0
Order By: Relevance
“…Granuloma formation in schistosomiasis is a manifestation of delayed-type hypersensitivity to antigenic material released by S. mansoni eggs that peaks at 8 weeks postinfection (16). Liver fibrosis is a complex process resulting from increased synthesis and deposition of extracellular matrix components (17).…”
Section: Discussionmentioning
confidence: 99%
“…Granuloma formation in schistosomiasis is a manifestation of delayed-type hypersensitivity to antigenic material released by S. mansoni eggs that peaks at 8 weeks postinfection (16). Liver fibrosis is a complex process resulting from increased synthesis and deposition of extracellular matrix components (17).…”
Section: Discussionmentioning
confidence: 99%
“…Given the controversial roles of type 1 and type 2 cytokines in the pathogenesis of schistosomiasis (24,30,31), we examined the regulatory role of IL-10 in mice that manifested extreme Th1-or Th2-producing phenotypes (17). For these studies, IL-10/IL-4-deficient and IL-10/IL-12-deficient mice were infected with 20 -30 S. mansoni cercariae, and disease progression was examined in detail during both the acute and chronic stages of infection and compared with that in WT mice as well as animals exhibiting single cytokine deficiencies.…”
Section: The Egg-induced Cytokine Response In Schistosomiasis Is Regumentioning
confidence: 99%
“…Therefore, the occurrence of this semi-aquatic rodent in endemic areas is a factor that makes it difficult to control this zoonosis (SOUZA et al, 1992;D'ANDREA et al, 2000;GENTILE et al, 2006). Cheever et al (1998) reported the formation of hepatic granulomas in mice infected by S. mansoni. Likewise, CostaSilva et al (2002), in a comparative study of natural and experimental infection by S. mansoni in N. squamipes, detected the presence of peri-ovular hepatic lesions in pre-granulomatous phases under natural conditions, while experimentally infected rodents showed a limited pattern of granulomas and a strong initial or peri-ovular inflammatory reaction 52 days after being infected.…”
Section: Introductionmentioning
confidence: 99%